(Re)pensar as imagens nas práticas escolares - Ferrarini, Maria Cristina Luiz (2014)
The main aim of this dissertation was to understand the perceptions of the educators involved in an investigation about the possibilities and importance of the use of visual culture images in the educational process within basic school spaces. The nature of the research was qualitative and exploratory. The empirical part was started by an extension course, a partnership between the Federal University of São Carlos and the local state school educational bureau, named: Image reading for medium and high school. Teachers lecturing at the four main areas of the national curriculum participated in the course. There were also school principals and pedagogical coordinators. From this group of educators, seven were selected to participate more directly of the investigation. The data collected were analyzed by the content analyses methodology, in which some aspects stood out, the ones we considered the obtained results: the cognitive development of the students and the application of specific school content has been one of the main image work objectives in the participants classrooms; such utilization occurs as a critical pedagogy strategy, directed mainly to perceptions of media influence; the school books available images have not been explored in all their possibilities, as knowledge facilitators and articulators towards critical attitudes; there is a content theorization need in critical perspectives, besides the thought diversity, fostered by collective appreciations of several images and artifact belonging to the visual culture, allowing the comprehension of plural thought importance and the difference concept, which may produce new basis to build a more democratic and inclusive basic school.